Adenosine-guided pulmonary vein isolation for the treatment of paroxysmal atrial fibrillation: an international, multicentre, randomised superiority trial. Issue 9994 (15th August 2015) - Macle, Laurent; Khairy, Paul; Weerasooriya, Rukshen; Novak, Paul; Verma, Atul; Willems, Stephan; Arentz, Thomas; Deisenhofer, Isabel; Veenhuyzen, George; Scavée, Christophe; Jaïs, Pierre; Puererfellner, Helmut; et al.
Summary: Background: Catheter ablation is increasingly used to manage atrial fibrillation, but arrhythmia recurrences are common. Adenosine might identify pulmonary veins at risk of reconnection by unmasking dormant conduction, and thereby guide additional ablation to improve arrhythmia-free survival. We assessed whether adenosine-guided pulmonary vein isolation could prevent arrhythmia recurrence in patients undergoing radiofrequency catheter ablation for paroxysmal atrial fibrillation. Methods: We did this randomised trial at 18 hospitals in Australia, Europe, and North America. We enrolled patients aged older than 18 years who had had at least three symptomatic atrial fibrillation episodes in the past 6 months, and for whom treatment with an antiarrhythmic drug failed. After pulmonary vein isolation, intravenous adenosine was administered. If dormant conduction was present, patients were randomly assigned (1:1) to additional adenosine-guided ablation to abolish dormant conduction or to no further ablation. If no dormant conduction was revealed, randomly selected patients were included in a registry. Patients were masked to treatment allocation and outcomes were assessed by a masked adjudicating committee. Patients were followed up for 1 year. The primary outcome was time to symptomatic atrial tachyarrhythmia after a single procedure in the intention-to-treat population. The trial is registered withClinicalTrials.gov, numberNCT01058980 . Findings: Adenosine unmasked dormant pulmonary vein conduction in 284 (53%) of 534 patients. 102 (69·4%) of 147 patients with additional adenosine-guided ablation were free from symptomatic atrial tachyarrhythmia compared with 58 (42·3%) of 137 patients with no further ablation, corresponding to an absolute risk reduction of 27·1% (95% CI 15·9–38·2; p<0·0001) and a hazard ratio of 0·44 (95% CI 0·31–0·64; p<0·0001). Of 115 patients without dormant pulmonary vein conduction, 64 (55·7%) remained free from symptomatic atrial tachyarrhythmia (p=0·0191 vs dormant conduction with no further ablation). Occurrences of serious adverse events were similar in each group. One death (massive stroke) was deemed probably related to ablation in a patient included in the registry. Interpretation: Adenosine testing to identify and target dormant pulmonary vein conduction during catheter ablation of atrial fibrillation is a safe and highly effective strategy to improve arrhythmia-free survival in patients with paroxysmal atrial fibrillation. This approach should be considered for incorporation into routine clinical practice. Funding: Canadian Institutes of Health Research, St Jude Medical, Biosense-Webster, and M Lachapelle (Montreal Heart Institute Foundation).